Desenvolvimento de aditivos bifuncionais derivados do cardanol hidrogenado para aplicação em mistura diesel/biodiesel - Nascimento, Tássio Lessa do (2023)
Biodiesel is used in the vehicular fleet through its insertion together with diesel, which has high oxidative stability when compared to this biofuel. However, in the diesel/biodiesel blend, instability to oxidation predominates, which in the long term can cause wear and/or corrosion in the mechanical devices of vehicles fueled with this combination. In this scenario, agents with antioxidant and lubricity properties stand out, in which a byproduct of the cashew nut processing industry, cardanol, is present in the Cashew Nut Liquid (CNSL). In the present study we aimed to evaluate the potential of hydrogenated cardanol, 3-pentadecylphenol (compound 1), and some of its derivatives as fuel additives. Tert-butyl chloride (2) was produced in the laboratory to be the alkylating agent to obtain 2-tert-butyl5-pentadecylphenol (3). The other additives synthesized were: 2-nitro-5-pentadecylphenol (4), diethyl-3-pentadecylphenyl phosphate (5), 3-pentadecylphenyl diphenyl (6), tri (3- pentadecylphenyl) phosphate (7), 2-tert-butyl-5-pentadecylphenyl diethyl phosphate (8), and 2-tert-butyl-5-pentadecylphenyl diphenyl phosphate (9). During the syntheses of these compounds, reproduced with modification, principles of green chemistry were employed. The reproduced compounds were characterized by Gas Chromatography Coupled to Mass Spectrometer (GC/MS) and by Infrared (IR) and Nuclear Magnetic Resonance (1H and 13C NMR) spectroscopies. The soy biodiesel used in the diesel/biodiesel blend in the ratio 8:2, was synthesized through the methyl route using the potassium methoxide catalyst, and was characterized according to the ANP Resolution No . 45 of 08/25/2014. The antioxidant activity of hydrogenated cardanol and its derivative compounds (2000 mg/kg), was evaluated using the DPPH• and Rancimat methods, and lubricity by the Four Ball technique. The results of the antioxidant analysis showed that all compounds stabilized the DPPH• radical, especially 3 (81.1), 1 (46.5), and 7 (43%) for the highest percentages of free radical reduction. In the Rancimat test, the compounds that showed the greatest increases in induction time were 7 (32.8%), 3 (31%), and 9 (31%). For lubricity, the 3- pentadecylphenyl diphenyl compound (6) provided the highest percentage (70.4%) of lubricity, observed as a result of its higher torque-reducing effectiveness when compared to the additive-free soy biodiesel. In a comprehensive way, the phosphorus additives (5, 7, 8 and 9) were the most efficient and represent a class of semi-synthetic eco-compatible compounds, therefore, they are inserted in the energy sector that seeks to develop efficient and low-polluting fuels, thus, if commercialized, they will add biotechnological value to the fuel industries.